Accident Analyses of Optimal Designed Primary Loop. Issue 1 (September 2020) - Chen, Lei; Song, Feifei; Jia, Zhen
Abstract: Through optimizing the operational and the structural parameters, the weight, volume or the efficiency. etc of primary loop can be imporved. To study the transient behaviours of the optimal scheme under desigend based accidents, we use RELAP5 code to build simulaiton model of the primary loop, and set conservative boudary conditions and initial conditions to make simulations of loss of feed water accident and station blackout accident for both of the optimal scheme and the prototype. The study shows that the core safety can be guaranteed under the accidents.